(untitled) (Research, Society and Development, 2021)
Analyze risks and situations before ergonomic performance of the teaching role. This is an exploratory, descriptive study with a quantitative approach, consisting of teachers from a Higher Education Institution, in the interior of the state of Ceará, as inclusion criteria are those who teach classes in the undergraduate course in nursing. The collection took place through the application of a questionnaire prepared by the authors, using the Ergonomic Analysis of Work, in a private environment, respecting privacy and confidentiality. The data were grouped and analyzed through the organization of central ideas about the presence of risks and situations before ergonomic and their main harm to the health of the teacher. It was possible to observe that mainly the environmental, physical and / or organizational characteristics of the workplace are relevant and relevant to the appearance or worsening of the symptoms reported by the teachers.